EFFECT OF SEED SOURCES (CUTTINGS AND TUBERS) ON GROWTH AND YIELDS RESPONSE OF G2 POTATO GRANOLA LEMBANG: PENGARUH SUMBER BENIH (STEK DAN UMBI) TERHADAP PERTUMBUHAN DAN HASIL KENTANG G2 GRANOLA LEMBANG - Ilmam Zul Fahmi; Rafi Akbar Pamungkas; Yogi Alfa Nanda Pradana (Universitas Wahid Hasyim, 2025)
Potato productivity in Indonesia remains relatively low at 13.38 t ha⁻¹, compared with its optimal potential yield of up to 26.5 t ha⁻¹. This low productivity is largely attributed to the use of poor-quality seed tubers, inefficient cultivation practices, and limited farmer access to appropriate technologies and production inputs. The present study aimed to evaluate the growth and yield performance of Generation-2 (G2) seed potatoes derived from stem cuttings and seed tubers of the Granola Lembang variety under field conditions in Pujon, Malang. The experiment was conducted using standard cultivation techniques, including the application of organic and inorganic fertilisers, hilling, irrigation, and integrated pest and disease management. Agronomic parameters observed included plant height, stem diameter, number of primary branches, number of leaves, number of tubers, and tuber weight per plant. Data were analysed using t-tests to compare the treatments. The results revealed significant effects of the treatments on all growth and yield parameters measured. T-test analysis showed p-values < 0.05 across all parameters at 56, 70, and 84 days after planting. These findings indicate that both stem cuttings and sprouted seed tubers can be effectively utilised for the production of G2 potato seed, thereby offering alternative approaches to improve seed availability and productivity in potato cultivation.